RESEARCH OF THE EFFICIENCY OF ONLINE TRAINING SESSIONS AMONG 10-13-YEAR-OLD CHESS PLAYERS - Leyla Dimitrova (Journal of Applied Sports Sciences, 2022)
The aim of the research was to establish the actual interrelations and interdependencies between the traditional (face-to-face) and online forms of chess training sessions among 10-13-year-old chess players. The research was done among 37 competitors with Elo rating 1050-1400 points from four chess clubs in Bulgaria. They were divided into two groups. In one of the groups, the sessions were conducted only online, and in the other group – only in a training hall. A unified lecture course was created for the purpose of the research. It consisted of the obligatory elements of two-component education – lectures on 15 basic chess topics (10 about chess tactics and 5 about chess strategy) and tests-exercises for each of them. At the end of the lecture course, through a suitable set of chess indexes, we measured the degree to which the material had been learnt by the participants in the two groups. The applied Student’s t-test for two independent samples showed that the difference in the results from the two forms of testing was insignificant, i.e., it was not a consequence from the form of testing but from fortuitous factors. The result from this research can help chess coaches working with this age group to take a much more professionally conscious choice regarding the degree of presence of the two types of chess practices during their training sessions.